Pee-cycling: Boosting fertilizer potential of human urine using urease-immobilized polymeric high internal phase emulsion - Sahin, Busra; Ozbey-Unal, Bahar; Arslan, Nida; Ciftci, Yelda Ozden; Keskinler, Bülent; Balçık, Çiğdem (Elsevier, 2025)
This study investigates the recovery of ammonium sulfate from human urine using urease immobilized on polymeric high internal phase emulsion (polyHIPE) support material and its potential as a fertilizer for durum wheat. Scanning electron microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FT-IR) analysis revealed structural changes in polyHIPE after treatment with glutaraldehyde, enhancing its pore structure. Optimal conditions for urease activity were found at pH 7 and 45 degrees C, with the immobilized enzyme retaining 53 % of its activity over 10 cycles and 50 % after 10 days at room temperature. X-ray diffraction confirmed the similarity of the recovered ammonium sulfate to commercial versions. As fertilizer, the recovered ammonium sulfate showed comparable results to commercial products in terms of plant growth, with no significant differences in height, spike length, or spikelets. Producing ammonium sulfate from abundant, cost-effective human urine provides a sustainable and economical alternative to synthetic fertilizers, supporting environmental and agricultural goals.
Keywords: Pee-cycling; Urease immobilization; Polymeric high internal phase emulsion; Ammonium sulfate recovery